Training, Remuneration and Teamwork as Predictors of Job Performance of Employees: An Insight from National Examinations Council, Nigeria - John Olayemi Okunlola (Research in Social Sciences and Technology- OpenED Network, 2023)
The impact of training, remuneration, and teamwork factors on job performance has been affirmed in the literature. However, not all organizations devote efforts to these critical variables of performance, which has led to employees' poor job performance. Hence, this study examined the influence of training, remuneration, and teamwork factors on job performance among employees of the National Examinations Council (NECO) of Nigeria. The study was located within a positivist paradigm that adopted a descriptive survey design. A purposive sampling technique was adopted in selecting 140 NECO employees, and a random sampling technique was employed to select 100 respondents from the total population of 1000 secondary school registrars. One research question was answered, while four hypotheses were tested in the study. Two research instruments were used for data collection. Data were analyzed using frequency count, percentage, Pearson product-moment correlation, and multiple regression statistical tools. The result showed that NECO employee job performance is excellent. There was a significant relationship between remuneration and job performance (R=0.864 (Sig, .023). There was also a significant relationship between teamwork and job performance R=2.072 (Sig, .022). In addition, a significant relationship existed between training and job performance R=1.143 (Sig, .008), and the combination of the independent variables is effective in predicting employee job performance (F(3,136 ) = 9.224, p< 0.05). Based on the result of the study, it was concluded that the independent variables are critical factors in determining the job performance of NECO employees in Oyo state, Nigeria. Hence, it was recommended that all these factors be given deserved attention and taken seriously by the management to get the best out of its employees.